Optimization of pharmacotherapies for ambulatory patients with heart failure and reduced ejection fraction is associated with improved outcomes. (1st January 2023) - Jarjour, Marilyne; Leclerc, Jacinthe; Bouabdallaoui, Nadia; Ahnadi, Charaf; Brouillette, Denis; de Denus, Simon; Fortier, Annik; Garceau, Patrick; Giraldeau, Geneviève; Lepage, Serge; Liszkowski, Mark; O'Meara, Eileen; et al.
Abstract: Background: In heart failure, specific target doses for each drug are recommended, but some patients receive suboptimal dosing, others are undertreated or remain chronically in a titration phase, despite having no apparent contraindication or intolerance. We assessed the association of different levels of adherence to guidelines with outcomes in patients with heart failure and reduced ejection fraction (HFrEF). Methods: Medical records of patients with HFrEF followed at our heart failure (HF) clinic for at least 6 months ( n  = 511) were reviewed and patients categorized as: 1) optimized (25.4%); 2) in-titration (29.0%); 3) undertreated (32.7%); and 4) intolerant/contraindicated (12.9%). Risk of mortality or HF events (hospitalization, emergency visit or ambulatory administration of intravenous diuretics) within one year was assessed using Cox regression models and Kaplan-Meier curves. Results: Compared to optimized patients, those intolerant (HR: 4.60 [95%CI: 2.23–9.48]; p  < 0.0001) had the highest risk of outcomes, followed by those undertreated (3.45 [1.78–6.67]; p  = 0.0002) and in-titration (1.99 [0.97–4.06]; p  = 0.0588). Overall predictors of outcomes included loop diuretics' use (4.54 [2.39–8.60]), undertreatment (2.38 [1.22–4.67]), intolerance/ contraindication to triple therapy (3.08 [1.47–6.42]), peripheral vascular disease (2.13 [1.29–3.50]) and NYHA class III-IV (1.89 [1.25–2.85]); all p  < 0.05. Conclusion: Level of adherence to guidelines is associated with outcomes, with intolerant/contraindicated patients having the worst prognosis and those undertreated and in-titration at intermediate risk compared to those optimized. Up-titration of therapy should be attempted whenever possible, considering patients' limitations, to potentially improve outcomes. Highlights: Level of adherence to GDMT for patients with HFrEF is associated with outcomes. Intolerance/contraindication to pharmacotherapy is a predictor of worse prognosis. Long titration or undertreatment carry a higher risk of events than optimization. Up-titration according to patients' limitations should be done to improve outcomes.